Planning process of sustainable village tourism masterplan based on local wisdom in Sutojayan Village, Malang Regency - Isnandar Isnandar; Joko Samodra; Muhammad Aris Ichwanto; Wahyu Sakti Gunawan Irianto; Salsabila Thifal Nabil Haq; Rian Syahmulloh Hendranawan; Luhur Adi Prasetya; Amir Rofiudin; Ary Agung Wibowo; Irva Widiyawati; Khusnul Muttaqiyah (Regional Development Information Center, Universitas Sebelas Maret, 2026)
This study examines the planning process of a sustainable village tourism master plan based on local wisdom in Sutojayan Village, Pakisaji District, Malang Regency. A deductive rationalistic approach was applied, with data collected through field observations, in-depth interviews, questionnaires, and Focus Group Discussions (FGDs) involving local residents, village officials, and community leaders. The results indicate that Sutojayan Village possesses considerable tourism potential derived from its natural landscapes, traditional agricultural practices, and local cultural assets. Community participation in the planning process reached 80%, while government support in the form of training programs and basic facility provision accounted for approximately 70%, highlighting the need for improvements in budget allocation and infrastructure quality. Key recommendations include the development of thematic tourism, enhancement of infrastructure capacity, tourism management training, and environmental education for younger generations. A well-structured master plan grounded in local wisdom is expected to promote sustainable tourism development and improve community welfare.